Challenging Traditional Fasting Protocols with New Data on Carbohydrate-Loaded Clear Fluids up to 2 Hours before Surgery - Roheena Wadud, Jawad Hameed, Amna Batool, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Preoperative fasting in the past only dictates that patients that are undergoing surgery should be nil per os (NPO) for at least 6 hours before the operation commences. However, new evidence suggests that pre-existing clear fluids loaded with carbohydrates up to two hours pre-surgery could provide various advantages such as enhanced glycaemia control and speedy recovery. Objective: To assess the safety and efficacy of carbohydrate-loaded clear fluids taken no longer than two hours before surgery against the traditional fasting procedures. Materials and Methods: A prospective, randomized controlled study was carried out at Anesthesia Department, Lady Reading Hospital-MTI Peshawar, Pakistan, from December, 2022 to May, 2023. Patients having elective minor surgeries are randomized to intervention (carbohydrate-loaded fluids) or control (standard NPO) groups. Postoperative complications, level of glycemic control, recovery times, and patient satisfaction were also measured. Results: The intervention group suffered from fewer complications, better glycemic control, speedier recovery, and greater patient satisfaction than the control group. Conclusion: Carbohydrate-loaded clear fluids up to two hours before surgery enhance recovery and reduce complications, supporting a shift in preoperative fasting guidelines. Keywords: Carbohydrate loading, preoperative fasting, surgical recovery, glycemic control, patient satisfaction, enhanced recovery.